Exploring The Nexus: Pathological Narcissism, Substance Abuse, and Self-Regulation as Predictors of Suicidal Ideation in College Students - Akanbi, Samuel Toyin (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
The study explored the predictors of suicidal ideation among university undergraduates focusing on the roles of narcissism, substance usage, and self-regulation. A correlational approach was adopted for the study. A total of 1,411 undergraduates selected through a multistage random sampling from three Nigerian universities participated in the study. Suicide Ideation Scale (α= .76), The Short Self-Regulation Questionnaire (α=.87), Drug Abuse Screening Test (α=.7), and Pathological Narcissism Inventory (α=.94) were used to gather information from the participants. Data collected were subjected to statistical screening through the Pearson Product Moment Correlation and multiple regression. The outcomes showed that a combination of the three main predictors explained a total of 32% (R2=.322; F(4,1406)= 166.557; p